Patient Self-worth and Communication Barriers to Trust of Israeli Patients in Acute-Care Physicians at Public General Hospitals. (November 2019) - Gabay, Gillie
Patient trust is positively related to health outcomes, but there remain barriers to patient trust in physicians. This narrative study analyzed patient experiences and highlights barriers to patient trust underlying communication with physicians in acute care. Snowball sampling was used. Informants were 12 participants, in poor physical health, upon discharge from a 3-week hospitalization in an acute-care setting at an Israeli public general hospital. Two narrative interviews were conducted with each participant upon and after discharge. Findings suggest presurgery barriers to trust (lack of acknowledgment of patient's crisis, underrating patient's autonomy, and use of unique empathy) and postsurgery barriers to trust (lack of attentive listening, lack of medical professionalism, and delegitimization to patients' self-alienation). Two common narrative identities emerged linking trust with self-worth. To build trust, physicians are called upon to extend their dedication from dedication to improve clinical outcomes to dedication to improve clinical outcomes and preserve patients' self-worth.